Does urbanisation lead to parallel demographic shifts across the world in a cosmopolitan plant? - Aude E. Caizergues; James S. Santangelo; Rob W. Ness; Fabio Angeoletto; Daniel N. Anstett; Julia Anstett; Fernanda Baena‐Diaz; Elizabeth J. Carlen; Jaime A. Chaves; Mattheau S. Comerford; Karen Dyson; Mohsen Falahati‐Anbaran; et al. (Molecular Ecology, 2024)
Urbanisation is occurring globally, leading to dramatic environmental changes that are altering the ecology and evolution of species. In particular, the expansion of human infrastructure and the loss and fragmentation of natural habitats in cities is predicted to increase genetic drift and reduce gene flow by reducing the size and connectivity of populations. Alternatively, the ‘urban facilitation model’ suggests that some species will have greater gene flow into and within cities leading to higher diversity and lower differentiation in urban populations. These alternative hypotheses have not been contrasted across multiple cities. Here, we used the genomic data from the GLobal Urban Evolution project (GLUE), to study the effects of urbanisation on non‐adaptive evolutionary processes of white clover ( Trifolium repens ) at a global scale. We found that white clover populations presented high genetic diversity and no evidence of reduced N e linked to urbanisation. On the contrary, we found that urban populations were less likely to experience a recent decrease in effective population size than rural ones. In addition, we found little genetic structure among populations both globally and between urban and rural populations, which showed extensive gene flow between habitats. Interestingly, white clover displayed overall higher gene flow within urban areas than within rural habitats. Our study provides the largest comprehensive test of the demographic effects of urbanisation. Our results contrast with the common perception that heavily altered and fragmented urban environments will reduce the effective population size and genetic diversity of populations and contribute to their isolation.

Population structure and genetic diversity of greater sage-grouse (Centrocercus urophasianus) in fragmented landscapes at the northern edge of their range - Krista L. Bush; Christopher K. Dyte; Brendan J. Moynahan; Cameron L. Aldridge; Heather S. Sauls; Angela M. Battazzo; Brett L. Walker; Kevin E. Doherty; Jason Tack; John Carlson; Dale Eslinger; Joel Nicholson; et al. (Conservation Genetics, 2011)